Effect of population growth on demand and water crisis in Universiti Malaysia Pahang - Nur Atiqah, Abu Bakar (2012)
This study was conducted with the demand; water crisis and consumptive water use at Universiti Malaysia Pahang Pekan Campus since it build. Increasing demand for water depends on population at UMP Pekan itself that increase rapidly in one year. The region around UMP Pekan also face water crisis and it affected also not only residents at UMP Pekan, but residents at Kuala Pahang. This study was conducted to identify the volume of the water demand and capacity at UMP Pekan Campus and also analyze the water demand and crisis for making a suggestion in future plan. The data was collected via interview with residents of UMP Pekan Campus, questionnaire developed for UMP Pekan's residents and also data collected from Jabatan Perbendaharaan dan Pengurusan Harta, Bahagian Pengurusan Pelajar and Pengurusan Air Pahang Berhad (P AIP). From the study, the real causes of water shortage that occur at UMP Pekan Campus was determined and also it concluded with the best solution to avoid the water crisis occur in the future.